The Conquest of Assyria - Larsen, Mogens Trolle, author.
1 online resource (408 pages)
Keywords: The Conquest of Assyria tells what must surely be one of the most romantic tales of archaeological endeavour. The great cities and ancient palaces of Mesopotamia had lain buried for over two millenia, and were all but forgotten, half remembered in the Hebrew Bible and Classical texts. This volume records the dramatic finds, the decipherment of the cuneiform system of writing and the rediscovery of a lost civilisation.